Total quality management influence the logistics performance of pharmaceutical industry in China - Hang, Su (2013)
One of key issues of china pharmaceutical industry is inefficient logistics. Logistics plays an important role in organization operating. Therefore, organization requires seeking the method to improve logistics performance. The purpose of this study was to investigate the relationship between total quality management and logistics performance in pharmaceutical industry in china. The sample of this study was the 121 employees of Furen pharmaceutical industry in Henan province, China. For this purpose survey method was used by questionnaire as instrument for data collection. In this study, regression analysis method and correlation analysis method are used to analysis the correlation between independent variables and dependent variable. The research results have shown that Furen pharmaceutical industry has high implementation in total quality management at current stage. Meanwhile, employee involvement, customer focus, leadership and continuous improvement as items of total quality management are significantly influence logistics performance. The study faced several limitations such as time constraints and budget constraints which limited this study only have one pharmaceutical industry. The finding of this study has some contributions for future research and organization’s logistics development